Integrated Digital Survey: The Roman Amphitheater of Suasa (Castelleone di Suasa, AN) - Francesca Bindelli; Alessandro Campedelli (Proceedings)
This paper discusses an experience developed as part of the 2021 Topographic Survey Workshop, organized by the Department of Cultural Heritage of Ravenna (University of Bologna) in the Roman city of Suasa (Castelleone di Suasa, AN), during which the potential of integrating photogrammetric and laser scanner surveys was explored in order to geometrically and morphologically characterize the remains of the Roman amphitheater.